Group hospital and surgical insurance: a case study on customer satisfaction towards the insurer / Muhammad Afiq Khalid - Khalid, Muhammad Afiq (Faculty of Business and Management, 2010)
Group Hospital and Surgical Insurance is a policy that is generally designed to cover the cost of private medical treatment, such as the cost of hospitalisation and healthcare services. The cost of getting hospitalized due to catastrophic illness can be astronomical and very few of us may be able to absorb the cost out of our own pocket. As such, UiTM’s employees as insured persons, expect to obtain the higher quality of services to attain their important needs .Therefore; the research is conducted to study the level of customers’ satisfaction on the Insurer for UiTM’s employees Universiti Teknologi Mara (UiTM) Melaka for both campuses, Universiti Teknologi Mara (UiTM) Alor Gajah Campus and Universiti Teknologi Mara (UiTM) City Campus Overall, most of employees agreed that they are neither satisfied nor dissatisfied with the product characteristics provided by the Insurer. There are several possible suggestions derived that can improve the product characteristics on the Group and Hospital Surgical Insurance scheme.